The Impact of Artificial Intelligence Technologies on Institutional Competitive Performance From 2024 to 2034 (مجلة إضافات إقتصادية, 2025)
This study explores the impact of Artificial Intelligence (AI) technologies on institutional competitive performance. It analyzes AI’s role in automating processes, reducing costs, improving efficiency, and supporting innovation, while also identifying adoption challenges. Findings show that AI capabilities, models, neural networks, and engines enhance efficiency, foster innovation, and strengthen competitive advantage through data-driven decisions and market prediction. However, risks include over-reliance on technology, data governance issues, ethical concerns, workforce adaptation, and regulatory complexities. The study recommends continuous improvement, robust training, interdisciplinary collaboration, and transparent data management to balance technological gains with human insight.Jel Classification Codes: C45, O47, O31